2014
DOI: 10.1111/maq.12076
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Narratives on Race and Health in Brazil

Abstract: In 2006, Brazil approved a groundbreaking policy aimed at reducing significant racial health inequalities among its citizens. Like health disparities programs in the United States, Brazil's policy is based on the assumptions that racial identity and racism are important health determinants and that citizens who identify as "black" suffer disproportionately from a number of health problems. How do these assumptions compare to Brazilian citizens' conceptions of racial identity and health inequalities? To address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…In two nationwide Brazilian studies, carried out in 2003 and 2013, the main reasons identified for the perception of discrimination in health services were poverty and social class 47,48 . The explicit mention of race/color was much lower, occupying fifth place in both studies, which is in line with other analyses of social perceptions of relationships between race/color and health in Brazil 49 . It is worth highlighting that Boccolini et al showed that, though women did not report race/color as the main reason for discrimination, in the multivariate analysis black-skinned women were the ones who reported discrimination most, albeit for reasons other than just race/color 48 .…”
Section: Black (%)supporting
confidence: 89%
“…In two nationwide Brazilian studies, carried out in 2003 and 2013, the main reasons identified for the perception of discrimination in health services were poverty and social class 47,48 . The explicit mention of race/color was much lower, occupying fifth place in both studies, which is in line with other analyses of social perceptions of relationships between race/color and health in Brazil 49 . It is worth highlighting that Boccolini et al showed that, though women did not report race/color as the main reason for discrimination, in the multivariate analysis black-skinned women were the ones who reported discrimination most, albeit for reasons other than just race/color 48 .…”
Section: Black (%)supporting
confidence: 89%
“…Not all of our nativo informants openly acknowledged the phenotypic and class differences between nativos and non-nativos as part of the symbolic value of non-nativos. This is consistent with patterns throughout Brazil in which low-income African-descendant Brazilians are less likely than middle-and upper-class black Brazilians to have racial consciousness and to acknowledge that racism exists (Pagano 2014). Employers likewise may not have been conscious of the fact that their employment preferences were based in race.…”
Section: Discussion: Symbolic Power In Brogodó's Touristscapesupporting
confidence: 81%
“…The ideology surrounding mestiçagem and discourses that compared racism in the United States to Brazil's nonracist society became central to the formation of the Brazilian nation-state and national identity (Pinho 2004(Pinho , 2009(Pinho , 2010. The intellectual discourse supporting mestiçagem and denying racism influenced Brazilians' perceptions of race and racism, their preference for discussing "color" instead of "race," and policies surrounding race (Pagano 2014;Sheriff 2001;Skidmore [1974Skidmore [ ] 1993. The Brazilian government used mestiçagem to justify discourses of a "racial democracy," a society free of discrimination based on skin color and other phenotypic traits, granting equal rights to all citizens.…”
Section: Race and Racism In Brazilmentioning
confidence: 99%
See 1 more Smart Citation
“…This specific history explains why critical and popular US discourses on race predominantly pivot on a binary black/white axis (Drake ). Comparative analyses of race in other geopolitical contexts, such as Latin America (Pagano ; Wade et al. ), the Caribbean (Castor ; Thomas ), or West Africa (Pierre ), reveal different systems of racialization and color/caste (A. Smedley ), social hierarchies, and patterns of racism.…”
Section: Interpreting Conceptualizations Of Race In Anthropologymentioning
confidence: 99%